Anthropomorphic images in rock art paintings and rock carvings - Meaden, George Terence,; Bender, Herman, (Archaeopress Archaeology, 2020)
In the realm of rock art, humanlike images appear widely through time and space from the Upper Palaeolithic to the Neolithic and Bronze Ages, and for some continents to later, yet still prehistoric, times. The artworks discussed in 'Anthropomorphic Images in Rock Art Paintings and Rock Carvings' range from paintings, engravings or scratchings on cave walls and rock shelters, images pecked into rocky surfaces or upon standing stones, and major sacred sites (among them Gobekli Tepe, Avebury, Stonehenge, and the Palaeolithic Chauvet Cave) in which the possibility exists of recovery of the meanings intended by the artists and sculptors.